2018
DOI: 10.1098/rstb.2018.0085
|View full text |Cite|
|
Sign up to set email alerts
|

ENSO effects on the transpiration of eastern Amazon trees

Abstract: Tree transpiration is important in the recycling of precipitation in the Amazon and might be negatively affected by El Niño–Southern Oscillation (ENSO)–induced droughts. To investigate the relative importance of soil moisture deficits versus increasing atmospheric demand (VPD) and determine if these drivers exert different controls over tree transpiration during the wet season versus the dry season (DS), we conducted sap flow measurements in a primary lowland tropical forest in eastern Amazon during the most e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 62 publications
4
33
0
Order By: Relevance
“…Here, we measured upper-canopy trees as these account for a very high proportion of the total forest biomass and transpiration (Brum et al, 2018). Here, we measured upper-canopy trees as these account for a very high proportion of the total forest biomass and transpiration (Brum et al, 2018).…”
Section: How Can We More Accurately Quantify the Contribution Of Fumentioning
confidence: 99%
“…Here, we measured upper-canopy trees as these account for a very high proportion of the total forest biomass and transpiration (Brum et al, 2018). Here, we measured upper-canopy trees as these account for a very high proportion of the total forest biomass and transpiration (Brum et al, 2018).…”
Section: How Can We More Accurately Quantify the Contribution Of Fumentioning
confidence: 99%
“…This suggests that trees may be prioritizing carbon production at the expense of risking great hydraulic damage. The largest trees were found to be responsible for the greatest proportion of transpiration flux [25] and were also shown to have the greatest change in mortality rate as a consequence of drought [27]. Shenkin et al [27] found a relationship between drought-induced mortality rates and tree heights in Amazonian trees, but a weaker relationship with crown exposure, suggesting a limited role for atmospheric demand and a strong impact of water supply on the risk of death.…”
Section: Field Studies Of Ecophysiology and Carbon Dynamicsmentioning
confidence: 99%
“…What is critical to interpreting changes in the signals from any of these variables over time is a clear understanding of which El Niñ o-mediated changes in climate are responsible for the observed variation in tree growth and carbon cycling. Brum et al [25] find that atmospheric water vapour deficit (VPD), rather than changes in soil moisture and precipitation, is the key driver of increasing dry season transpiration during the 2015/16 El Niñ o in a site in eastern Amazonia. Fontes et al [28] find sharp drops in water flux through trees, associated with drops in both leaf and xylem safety margins.…”
Section: Field Studies Of Ecophysiology and Carbon Dynamicsmentioning
confidence: 99%
“…Plantation trees experience similar meteorological effects as upper canopy trees experience in secondary forests. Changes in vapor pressure deficit (VPD), temperature, precipitation, and radiation have all been shown to affect plant water use at hourly, daily, and monthly timescales (Bretfeld et al, 2018;Brum et al, 2018). There are often species-specific thresholds where plant water use begins to decline in response to high VPD, radiation, or temperature (Sinacore et al, in review), which often leads to reduced tree water use and stand transpiration during droughts (Brum et al, 2018;Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in vapor pressure deficit (VPD), temperature, precipitation, and radiation have all been shown to affect plant water use at hourly, daily, and monthly timescales (Bretfeld et al, 2018;Brum et al, 2018). There are often species-specific thresholds where plant water use begins to decline in response to high VPD, radiation, or temperature (Sinacore et al, in review), which often leads to reduced tree water use and stand transpiration during droughts (Brum et al, 2018;Zhang et al, 2018). With predicted increases in temperature, in particular, understanding at what threshold tree water use begins to decline at high temperatures and VPDs is crucial for modeling future stand and landscape level responses to a changing climate.…”
Section: Introductionmentioning
confidence: 99%